Two-color nonlinear resonances in betatron oscillations of laser accelerated relativistic electrons - M. Lamač; U. Chaulagain; L. Jurkovičová; J. Nejdl; S. V. Bulanov (Physical Review Research, 2021)
X-ray radiation from laser wakefield accelerated (LWFA) electrons provides a collimated broadband femtosecond x-ray source with micron-scale source size. However, the photon flux is still inadequate for a range of applications. By interaction of LWFA relativistic electrons with the second and the third harmonic of the laser driving the wakefield, we report more than an order of magnitude enhancement of photon flux emitted by the electrons undergoing betatron oscillations resonant with the harmonics. This phenomenon is demonstrated with analytical and numerical models, as well as particle-in-cell simulations.